Synthesis of Some 1,3,4-Thiadiazoline Derivatives - Kabilan, S.; Ramalingan, C.; Balasubramanian, S. (Asian Journal of Chemistry, 2010)
Some 4-acetyl-2-(acetylamino)-Δ2-1,3,4-thiadiazoline derivatives have been synthesized by cyclisation of thiosemicarbazones of some acyclic and cyclic betones using acetic anhydride and are fully characterized by their physical and spectral data.